Comparative effectiveness of tenofovir versus entecavir in patients with hepatitis B virus-related cirrhosis in Taiwan: a retrospective cohort study - Huang, Yu-Han; Shen, Chuan-Wei; Chen, Chung-Yu; Bair, Ming-Jong (Frontiers in Pharmacology, 2023)
Background: Tenofovir and entecavir demonstrated substantial effectiveness in the reversion of fibrosis and reversed cirrhosis in patients with hepatitis B virus (HBV)-related cirrhosis. However, there has not been a definitive conclusion regarding the association between entecavir and tenofovir on the risk of cirrhosis-related complications. Therefore, this study aimed to investigate the comparative effectiveness between tenofovir and entecavir in HBV-related cirrhosis patients. Methods: This was a retrospective study using Taiwan’s Health Insurance Research Database. We enrolled newly diagnosed HBV-related cirrhosis patients who initiated entecavir and tenofovir between 2011 and 2019. Treatment groups were determined by the initial HBV antiviral medication prescribed. The primary composite outcome was the development of hepatocellular carcinoma (HCC), death from any causes, and liver transplantation. The secondary outcomes included all the individual components of the primary outcome. The incidence rate was calculated for each outcome for both treatment groups using the Fine–Gray subdistribution hazard models. Propensity score adjustment was used to balance treatment groups. Results: A total of 7,316 propensity score-matched treatment-naïve patients and 3,524 propensity score-matched treatment-experienced patients were included. Within treatment-naïve patients, those receiving tenofovir showed significantly lower hazards of developing the composite outcome (HR, 0.79; p < 0.0001), hepatocellular carcinoma (HR, 0.86; p = 0.027), mortality (HR, 0.75; p < 0.0001), and liver transplantation (HR, 0.70; p = 0.0189) than those receiving entecavir. As for treatment-experienced patients, tenofovir was associated with a significantly lower risk of the composite outcome (HR, 0.82; p = 0.0033) and hepatocellular carcinoma (HR, 0.60; p < 0.0001), but it did not show a significantly different risk of all-cause mortality (HR, 0.93; p = 0.3374) or liver transplantation (HR, 1.17; p = 0.5112) compared to entecavir. Conclusion: Tenofovir presented a significantly lower incidence of cirrhosis-related complications than entecavir in patients with hepatitis B virus-related cirrhosis. However, no statistically significant difference in death and liver transplantation was seen in treatment-experienced patients.